Cabozantinib, a Multityrosine Kinase Inhibitor of MET and VEGF Receptors Which Suppresses Mouse Laser-Induced Choroidal Neovascularization - Zhang, Xiaoli (J Ophthalmol, 2020)
Choroidal neovascularization (CNV) is a leading cause of blindness in the elderly in developed countries and is particularly associated with age-related macular degeneration (AMD). Cabozantinib (CBZ) hinders the activation of multiple receptor tyrosine kinases involved in tumor angiogenesis, such as hepatocyte growth factor receptor (MET) and vascular endothelial growth factor receptor 2 (VEGFR2). We aimed to investigate the role and mechanism of CBZ in a mouse laser-induced CNV model. In zebrafish embryos, CBZ perturbed intersegmental vessel (ISV) formation without obvious neurodevelopment impairment. In the mouse laser-induced CNV model, phosphorylated hepatocyte growth factor receptor (p-MET) and phosphorylated vascular endothelial growth factor receptor 2 (p-VEGFR2) were increased in the CNV region. CBZ intravitreal injection or oral gavage alleviated CNV leakage and the CNV lesion area without obvious intraocular toxicity, as well as disturbed the phosphorylation of MET and VEGFR2. Additionally, CBZ downregulated the expression of the hepatocyte growth factor (HGF) with no effect on the expression of the vascular endothelial growth factor (VEGF). CBZ downregulated HGF, p-MET, and p-VEGFR2 expressions in vitro, as well as inhibited the proliferation, migration, and tube formation of b-End3 cells. In summary, CBZ alleviates mouse CNV formation possibly via inhibiting the activation of MET and VEGFR2. The findings provide a novel potential therapy method for CNV patients.